2014
DOI: 10.1007/s12178-014-9212-4
|View full text |Cite
|
Sign up to set email alerts
|

The patella in total knee arthroplasty: to resurface or not is the question

Abstract: The decision to resurface the patella during total knee arthroplasty remains controversial. Even though some surgeons routinely resurface the patella to avoid the increased rates of postoperative anterior knee pain and reoperation for secondary resurfacing, others selectively resurface based on the presence of anterior knee pain, notably damaged articular cartilage, inflammatory arthritis, isolated patellofemoral arthritis, and patellar subluxation and maltracking. The anatomy and biomechanics of the patellofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 61 publications
0
46
0
3
Order By: Relevance
“…Data from a 2009 Norway arthroplasty registry showed 2.4% of patients received a patellar component, while this number was 80% in a Danish Knee Arthroplasty Registry and over 90% in North American registries. [2,22] Literature supporting both clinical practices is immense and varies even within each country with the surgeon choice to resurface owing ultimately to a combination of education, clinical evidence, specific implant design, and cultural influence. Emerging data and meta analysis suggests maintaining the native patella in TKA has no influence on clinical outcome measures or patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a 2009 Norway arthroplasty registry showed 2.4% of patients received a patellar component, while this number was 80% in a Danish Knee Arthroplasty Registry and over 90% in North American registries. [2,22] Literature supporting both clinical practices is immense and varies even within each country with the surgeon choice to resurface owing ultimately to a combination of education, clinical evidence, specific implant design, and cultural influence. Emerging data and meta analysis suggests maintaining the native patella in TKA has no influence on clinical outcome measures or patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, between 2% and 90% of orthopedic surgeons choose to routinely resurface the patel-la. [1][2][3] The Australian National Joint Replacement Registry reported that 49.5% of TKAs in 2010 had the patella resurfaced, whereas a study using the joint registry in Norway reported that only 2.6% of all TKAs were done with a patellar resurfacing. 4,5 Advocates for patellar resurfacing claim that it may prevent the need for reoperation, address patellofemoral arthritis, improve the functional outcomes, and decrease the chance of developing anterior knee pain that is commonly associated with patellar non-resurfacing.…”
mentioning
confidence: 99%
“…4,5 Advocates for patellar resurfacing claim that it may prevent the need for reoperation, address patellofemoral arthritis, improve the functional outcomes, and decrease the chance of developing anterior knee pain that is commonly associated with patellar non-resurfacing. 1,[6][7][8] The Insall-Burstein design, created in 1974 (Zimmer, Warsaw, Indiana), was the first construct that allowed surgeons to proceed with resurfacing using a polyethylene dome 1 and was introduced to address the high incidence of patello-femoral complications. [9][10][11] However, with the introduction of designs that reconstruct the patello-femoral articulating surface, there was an inadvertent increase in a new generation of postoperative complications, such as patellar fracture, decreased range of motion (ROM), polyethylene wear, component loosening, polyethylene fracture, and patellar clunk syndrome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With primary total knee arthroplasty, there are three schools-of-thought about the patella: always resurface, never resurface or selectively resurface (bearing in mind the patient's articular cartilage, and patellofemoral congruence at the time of surgery) 1. In Scandinavia, about 2% of patellas are resurfaced (according to knee arthroplasty registries), while in USA more than 90% of patients get a patellar button.…”
mentioning
confidence: 99%